PEMANFAATAN SENI RUPA SEBAGAI MEDIA PEMBELAJARAN MATERI SOSIAL BUDAYA PADA IPAS DI KELAS IV SD NEGERI 01 SIJERUK - Deswa Havid Fernando; Deni Setiawan (Comm-Edu (Community Education Journal), 2026)
This research is motivated by the importance of using learning media appropriate to the characteristics of elementary school students in science learning, particularly in abstract socio-cultural material. This study aims to describe the use of fine art as a learning medium for socio-cultural material in science in fourth-grade students at SD Negeri 01 Sijeruk. The study employed a qualitative, descriptive approach. The subjects consisted of one fourth-grade teacher and eight students. Data collection techniques included observation, semi-structured interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results indicate that fine arts are utilized through visual media in the form of cultural images and visual displays using IFP TV. The use of visual media helps teachers explain abstract material more concretely. Most students show increased learning engagement, motivation, and understanding of the material. Around 6–7 out of 8 students show a positive response to the use of visual media in learning. In addition, the use of visual media helps improve students' focus, memory, and interest in learning. This study concludes that the use of fine arts based on visual media and technology effectively supports science learning on socio-cultural material and improves the quality of student learning engagement.